The Impact of the Free Nutritious Meal Program on Reducing Stunting and Household Food Expenditure in West Sumatra, Indonesia - Rina Susanti; Engla Desnim Silvia; Deni Amelia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the impact of the Free Nutritious Meal Program (MBG) on reducing stunting rates and reducing household food expenditure in Indonesia, focusing on West Sumatra. The MBG program is one of the government’s efforts to improve the nutritional status of vulnerable groups, particularly pregnant women, breastfeeding mothers, and young children, as well as reduce the economic burden of household food expenditure. This study uses a quantitative approach with a descriptive design, combining secondary data analysis from BPS and Kemenkes, along with primary data collected through a survey of 218 respondents who participated in the MBG program in the region. The results of the study indicate that participation in the MBG program has a significant impact on reducing stunting and reducing household food expenditure. The program not only improves the nutritional intake of families but also alleviates the food expenditure burden, which has been the largest economic challenge for many families, particularly those in low-income and vulnerable categories. Linear regression analysis and Structural Equation Modeling (SEM-PLS) were used to test the relationships among the variables, with results showing significant path coefficients between participation in the MBG program and both stunting reduction and food expenditure reduction. This study provides empirical evidence regarding the effectiveness of the MBG program in reducing stunting and improving household economic resilience, and offers recommendations for the government to expand the program’s coverage across Indonesia to achieve more optimal stunting reduction targets.